Building Minimum Viable Product (MVP) for Dance Cover Group of Haru Entertainment - Hanifinsani Muhammad, Dhahana; Aldianto, Leo (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Haru Entertainment is a performance based company that have 3 phase of business growth. For each phase, there are investing, promoting and decline period. Currently the company is on the investing period of dance cover focused phase. One of the activity in the investing period is making Minimum Viable Product (MVP). This research conducted in qualitative method using semi-structured interview to gather information about audience’ preference towards dance cover video. The audience’ preference is used for the researcher to create dance cover video to be tested. The test is to conclude id the video already reach MVP or not by testing the value and growth hypothesis. The value hypothesis tested using video scoring test and the growth hypothesis is tested by tracking the number of views on Youtube. By using the current company resources, Haru Entertainment is unable to create MVP for dance cover video and need to do next iteration using insight from the interview conducted. Keywords:  Dance Cover, Growth Hypothesis, MVP, Performance, Value Hypothesis